Prosedur Pengambilalihan Obyek Jaminan Hak Tanggungan dalam Masalah Kredit Macet - Triamy Rostarum (Universitas Batanghari Jambi, 2018)
This research aims to find out that the objects of collateral that have experienced credit or credit can be taken over by PT. Bank Mandiri (Persero) Tbk Branch of Jambi, and knowing the movement of Land Officials (PPAT) in the making of guarantees taken over by PT. Bank Mandiri (Persero) Tbk Jambi Branch. The research method used was disciplinary. The results of the research were done after the execution of the insurance coverage through auction and not to sell the news to PT. Bank Mandiri (Persero) Tbk Jambi branch can carry out the takeover of insurance coverage or as an ODA through auction by signing the takeover agreement between the bank and the facility or making news about the settlement of the February 2016 debt. The role of the PPAT is to create a Sales Act (AJB) which is the legal basis for the right to transfer land rights in the takeover of insurance benefits.